Discussion of the effects of corporate governance on firms’ credit ratings - Weber, Joseph (Journal of Accounting and Economics, 2006)
Ashbaugh-Skaife, Collins, and LaFond [2006. The effects of corporate governance on firms’ credit ratings. Journal of Accounting and Economics (this issue)] find that better governed firms receive better credit ratings and poor governance costs the median speculative grade firm $38 million in excess interest. They also find that managers choose to be poorly governed to expropriate wealth. The results from the primary analysis are persuasive, leaving little doubt on whether ratings agencies value corporate governance. However, the authors’ estimate of the economic costs of poor governance is likely to be overstated. Despite the evidence on the costs of poor governance, the final analysis leaves the question as to why firms choose to be poorly governed largely unanswered.